2013
DOI: 10.1063/1.4792704
|View full text |Cite
|
Sign up to set email alerts
|

Self-contact thin-film organic transistors based on tetramethyltetrathiafulvalene

Abstract: Carrier injection from organic contacts to tetramethyltetrathiafulvalene (TMTTF) is investigated in the thin-film transistors. When 7,7,8,8-tetracyano-p-quinodimethane (TCNQ) is patterned on a TMTTF film, the resulting (TMTTF)(TCNQ) works as highly conducting source and drain electrodes. Such self-contact transistors, in which the organic material constructing the active layer is selectively transformed to the contacts, have achieved low contact resistance and high performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…TTF‐TCNQ is the most common organic metal, and it has been used as electrodes in both p‐type and n‐type OFETs of various TTF derivatives, pentacene, copper‐phtalocianyne, DBTTF‐TCNQ, and fluorinated copper‐phtalocianyne . Selective deposition of TCNQ over the organic semiconductor tetramethyltetrathiafulvalene (TMTTF) or hexamethylenetetrathiafulvalene (HMTTF), led to inter‐diffusion and “on the spot” mixing between the two species, leading to the formation of the organic electrode in self‐contact transistors . These devices produced the lowest contact resistance ( R C W = 80 kΩ cm) compared to Au ( R C W = 3600 kΩ cm), and even the organic metal TTF‐TCNQ, when this was used as a stand‐alone contact ( R C W = 200 kΩ cm) (Figure b).…”
Section: Reducing Contact Resistance: Electrode Design and Beyondmentioning
confidence: 99%
See 1 more Smart Citation
“…TTF‐TCNQ is the most common organic metal, and it has been used as electrodes in both p‐type and n‐type OFETs of various TTF derivatives, pentacene, copper‐phtalocianyne, DBTTF‐TCNQ, and fluorinated copper‐phtalocianyne . Selective deposition of TCNQ over the organic semiconductor tetramethyltetrathiafulvalene (TMTTF) or hexamethylenetetrathiafulvalene (HMTTF), led to inter‐diffusion and “on the spot” mixing between the two species, leading to the formation of the organic electrode in self‐contact transistors . These devices produced the lowest contact resistance ( R C W = 80 kΩ cm) compared to Au ( R C W = 3600 kΩ cm), and even the organic metal TTF‐TCNQ, when this was used as a stand‐alone contact ( R C W = 200 kΩ cm) (Figure b).…”
Section: Reducing Contact Resistance: Electrode Design and Beyondmentioning
confidence: 99%
“…b) Contact resistance in tetramethyltetrathiafulvalene OFETs with Au, and CTs source and drain contacts. Reproduced with permission . Copyright 2013, AIP Publishing.…”
Section: Reducing Contact Resistance: Electrode Design and Beyondmentioning
confidence: 99%
“…41 The strategy took into account the following considerations: (i) the same organic molecule can work not only as the active layer in organic transistors but also as the electrode in the form of the CT salt, and (ii) it had been previously shown that at the interface between TTF derivatives and TCNQ single crystals charge transfer occurs with the consequent formation of a conduction channel. 41 The strategy took into account the following considerations: (i) the same organic molecule can work not only as the active layer in organic transistors but also as the electrode in the form of the CT salt, and (ii) it had been previously shown that at the interface between TTF derivatives and TCNQ single crystals charge transfer occurs with the consequent formation of a conduction channel.…”
Section: Evaporated Ct Saltsmentioning
confidence: 99%
“…6). [26][27][28][29] The resulting reduced Schottky barrier is another origin of the better performance of the (TTF)(TCNQ)-based transistors. [26][27][28][29] The resulting reduced Schottky barrier is another origin of the better performance of the (TTF)(TCNQ)-based transistors.…”
Section: Transistor Characteristicsmentioning
confidence: 99%